Relationship Between Pesticide Exposure and Neurobehavioral Disorders in Farmers - Miftahul Jannah, Indah (Universitas Airlangga, 2024)
Introduction: Pesticides are chemicals used to eradicate pests such as insects that damage crops and agricultural products. Farmers often do not realize that the benefits of pesticides are important for agriculture but also have dangerous risks. If farmers are constantly exposed to pesticides this can cause neurological diseases. The purpose of this study was to determine the relationship between exposure to pesticides and neurobehavioral disorders in farmers. Methods: The authors of this study conducted research using a systematic literature review on publications published in the last 5 years on two databases namely Google Scholar and Scopus using the keywords pesticides, neurobehavioral, and farmers. The literature review was conducted based on issues, methodology, similarities and further research proposals. The population was all farmers in Indonesia who work with pesticides on their crops. Results: Three of the four articles found reported that pesticide exposure and duration of action were associated with neurobehavioral events whereas one article did not state any association between these variables. Some neurobehavioral symptoms caused by pesticide exposure are dizziness, difficulty sleeping, and difficulty concentrating. Conclusion: The use of pesticide content must be balanced to minimize the risks caused by exposure. Farmers also have to get enough rest to restore the function of the cholinesterase enzyme in the blood. It can be concluded that exposure to pesticides is associated with neurobehavioral events in farmers.